Peningkatan Praktik Perawatan Payudara Pada Ibu Hamil Melalui Penyuluhan Kesehatan - Catur Wulandari (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Many mothers feel that they have failed to give exclusive breastfeeding to their babies because of errors and lack of information previously obtained. The purpose of this study was to determine the increase in breast care practices in third trimester pregnant women. This study uses a pre-experimental research design with a One Group Pretest-Postest approach. The research sample was 32 pregnant women obtained by purposive sampling technique. Data analysis used Wilcoxon statistical test with 0.05. The practice of breast care in third trimester pregnant women with a sufficient percentage then increased to good after being given health education. Statistical test obtained p value 0.000 which means there is an increase in breast care in third trimester pregnant women after being given health education. The practice of breast care in third trimester pregnant women if done properly and correctly, then the mother can breastfeed well after giving birth so that the nutritional needs of the child can be met.